Answer:
(-2, -2) is not a solution of the system of linear equations.
The graph is shown below:
The solution is (x, y) = (3, 1)
Step-by-step explanation:
Given the system of equations below:
![\begin{gathered} y=-(1)/(3)x+2 \\ \\ y=x-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/z9c1hbdso2c2gd0271xo5x1778zfmdtokw.png)
Suppose (-2, -2) satisfy these equations, then substitution x = -2, and y = -2 in each equation makes the left-hand side equal to the righ-hand side.
For the first equation:
![\begin{gathered} -2=-(1)/(3)(-2)+2 \\ \\ -2=(8)/(3) \\ \\ \text{But} \\ -2\\e(8)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hkj4mt1m2a1xtxwl9winv6bj9lz30k2rbd.png)
Therefore, this is sufficient to say that (-2, -2) is not a solution of the system of linear equations